Communicative Willingness in Dialogic Feedback: A Relational Extension of Feedback Literacy - Daniswara, Landry Dwiyoga (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Dialogic feedback assumes that students will respond to evaluative comments through clarification, negotiation, or further discussion. However, students do not always turn internal feedback processing into visible dialogue, especially in hierarchical performance settings where speaking may feel risky. This study examined how undergraduate debaters constructed communicative willingness when responding to coach feedback and aimed to extend feedback literacy theory by theorising this relational decision point. Methodology: This study used a constructivist grounded theory design. Twelve second and third-year undergraduate debaters were selected through purposive sampling from a one-semester university debate preparation program. Data were generated through two semi-structured interviews with each participant, observations of 16 feedback sessions, and relevant artefacts such as feedback sheets and notes. Analysis involved initial coding, focused coding, constant comparison, memo writing, and theoretical integration. Main Findings: Students' communicative willingness developed through an iterative process of interpreting feedback, regulating affect, assessing relational safety, negotiating possible consequences, and then enacting or withholding dialogue. Silence did not automatically indicate disengagement, because many students continued reflecting on and using feedback privately. Communicative willingness increased when prior interactions suggested that students' voices would be received respectfully. Novelty/Originality of this study: This study introduces communicative willingness as a relationally constructed mediating process between managing affect and dialogic enactment within feedback literacy. It shows that dialogic opportunities alone do not guarantee participation because students also judge safety, legitimacy, and exposure before speaking.